Anti-frosting and defrosting performance of chemically modified super-nonwettable carbon soot coatings. (12th October 2020) - Esmeryan, Karekin D; Gyoshev, Stanislav D; Castano, Carlos E; Mohammadi, Reza
Abstract: The inherent hydrophilicity of a variety of heat exchanging industrial appliances, including air-conditioners, refrigerators or heat pumps, is a highly-beneficial platform for the accumulation of frost at negative surface temperatures, dramatically aggravating the efficient device operation in terms of heat transfer and energy consumption. Here, we introduce experimental data from pioneering research on the frosting/defrosting behavior of chemically modified super-nonwettable soot—one of the very few materials providing scalability, satisfactory mechanical durability, icephobic and anti-bioadhesion properties simultaneously. The analysis of the anti-frosting/defrosting performance of three groups of soot coatings, obtained by treating the pristine samples with alcohol, fluorocarbon or silver hydrogen fluoride, reveals that the frost incipiency on the soot can be efficiently controlled by tailoring its chemistry and porosity. In turn, the super-nonwettable material is capable of delaying the onset of vapor condensation and frosting to supercooling degrees of 8.4 °C and 15.8 °C, accordingly, and maintaining relatively large frost-free halos up to −20 °C. Moreover, the onset of soot defrosting is accelerated by a factor of 35 compared to a bare Cu substrate, demonstrating extremely low ice adhesion forces and strong potential of the soot coatings for passive icing protection of many cryogenic facilities.